Estudo da reação tecidual à administração intraperitoneal de polimetilmetacrilato (PMMA) em ratos da linhagem Wistar - Menezes, Fernanda Carrilho de (2009)
This experimental study aims to analyze the responses and tissue migration of Polymethylmetacrylate (PMMA) after implantation in the peritoneal cavity of rats. Methods: We used 80 male Wistar rats, adult, weighing between two hundred and ninety-four hundred grams, distributed in randomly in 4 groups: Group in which it was administered 0.4 ml of 0.9% saline S4 (n = 20), group which was administered in 2 ml of 0.9% saline S2 (n = 20), in which group was given 0.4 ml of PMMA P4 (n = 20), group which was administered in 2 ml P2 PMMA (n = 20) for each experimental period. These in turn were divided into 4 subgroups according to the day of euthanasia, 1, 7, 14 and 28 days. Results: There was a predominance in all the times the procedure, the inflammatory reaction mild, rich in histiocytes in the peri-capsular organs studied. The giant cells were seen from the 7th day. Cells foreign body type was more common in the group in which PMMA is injected with a higher period of time. There was an increased number of fibroblasts in the region studied peri-capsular bodies throughout the time of the experiment. The presence of blood vessels was higher in groups where implanted PMMA. Greyish material was identified, compatible with PMMA, in 29 cases. Conclusion: There was no migration of PMMA to parenchymal organs like liver, spleen, lungs and kidneys after intraperitoneal administration at the abdomen in rats. The microparticles of PMMA, when found, were located mainly in the peri-capsular bodies. Changes in tissue organs such as liver, spleen and kidneys were similar, independent of the volume of PMMA injected into the peritoneal cavity.